Workers' Moral Hazard and Insurer Effort in Disability Insurance - Pierre Koning; Max van Lent (Institute of Labor Economics (IZA), 2022)
Disability Insurance (DI) may affect workers' outcomes such as their probability to enter DI, to recover, and their employment. Supplementary insurance may increase these moral hazard effects, but also increases the financial gains of private insurers to reduce benefit costs. With increased insurer activities to prevent and reintegrate workers, the overall effects of increased insurance coverage on workers' outcomes are thus ambiguous. This paper aims to separate worker and insurer responses to increased insurance, using unique administrative data on firms' supplementary DI insurance contracts. Using a Two-Way Fixed-Effects model on the sickness and employment rates of worker cohorts with and without supplementary contracts at some point in time, we find that insurer efforts compensate workers' moral hazard effects.
Keywords: G22; G52; J3; J21; 330; disability insurance; private insurance; moral hazard; insurer effort; return-to-work policies